Current trends in currency risk management by Polish shipbuilding enterprises - Kazojć, Katarzyna; Miciuła, Ireneusz (Aktualne trendy w zarządzaniu ryzykiem walutowym przez polskie przedsiębiorstwa stoczniowe, 2019)
The article presents modern trends related to the development of currency risk management methods and the opportunities and benefits associated with their implementation. Risk is a factor that should be considered when conducting business. Because economic decisions should be made in accordance with the economic calculation taking into account the opportunity costs and the effects of internal and external factors. To emphasize the importance of this issue, it is worth noting that currency risk can be the cause of both significant losses and large profits, as evidenced by numerous cases in real economic practice. Actions taken to manage currency risk increase the company's financial security. The article presents the currency risk control system on the example of Polish shipbuilding companies. At the same time, contemporary solutions used in shipbuilding enterprises in Poland were assessed together with an assessment of their effectiveness
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 2, s. 165-182
Keywords: currency risk; current trends in management; shipbuilding enterprises; financial risk; shift of economic circumstances; risk management; ryzyko walutowe; aktualne trendy w zarządzaniu; przedsiębiorstwa stoczniowe; ryzyko finansowe; zmiana warunków ekonomicznych; zarządzanie ryzykiem